2012
DOI: 10.1029/2012gl051409
|View full text |Cite
|
Sign up to set email alerts
|

The natural greenhouse effect of atmospheric oxygen (O2) and nitrogen (N2)

Abstract: [1] The effect of collision-induced absorption by molecular oxygen (O 2 ) and nitrogen (N 2 ) on the outgoing longwave radiation (OLR) of the Earth's atmosphere has been quantified. We have found that on global average under clear-sky conditions the OLR is reduced due to O 2 by 0.11 Wm À2 and due to N 2 by 0.17 Wm À2 . Together this amounts to 15% of the OLR-reduction caused by CH 4 at present atmospheric concentrations. Over Antarctica the combined effect of O 2 and N 2 increases on average to about 38% of CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…More recent measurements of collision-induced absorption typically use cavity ringdown spectroscopy to observe the weak collision-induced signal by achieving long path lengths [3][4][5][6][7][8][9][10][11] , rather than high pressures 12,13 . Roto-translational collision-induced absorption is important for the atmospheric heat balance 14 , and electronic transitions in O 2 , such as the A-band…”
mentioning
confidence: 99%
“…More recent measurements of collision-induced absorption typically use cavity ringdown spectroscopy to observe the weak collision-induced signal by achieving long path lengths [3][4][5][6][7][8][9][10][11] , rather than high pressures 12,13 . Roto-translational collision-induced absorption is important for the atmospheric heat balance 14 , and electronic transitions in O 2 , such as the A-band…”
mentioning
confidence: 99%
“…The concentrations of the second two gases may be treated as fixed both spatially and over the timescales commonly considered by climate models. O 2 is important mainly in the shortwave but reduces outgoing longwave radiation (OLR) by around 0.11 W m −2 globally (Höpfner et al, 2012). Absorption by N 2 is ignored by most operational radiation schemes, yet it reduces OLR by around 0.17 W m −2 (Höpfner et al, 2012) and, as will be shown in Sect.…”
Section: Which Gases?mentioning
confidence: 91%
“…Despite their small areal extent, rivers are increasingly recognized as significant hot spots for global carbon (C) and nitrogen (N) degradation and associated greenhouse gas emissions (Battin et al, ; Gomez‐Velez et al, ; Höpfner et al, ; Hotchkiss et al, ; Peyrard et al, ). The significance of biogenic CO 2 and N 2 gas production due to heterotrophic microbial activity in rivers and associated hyporheic zones to the overall carbon balance of rivers is poorly quantified, yet net heterotrophy is estimated to be 0.32 Pg C yr −1 , with half of terrestrial organic carbon stored or transformed in aquatic systems (Battin et al, ).…”
Section: Introductionmentioning
confidence: 99%